NAI2 Is an Endoplasmic Reticulum Body Component That Enables ER Body Formation in Arabidopsis thaliana - Yamada, Kenji (American Society of Plant Biologists, 2008)
Plants develop various endoplasmic reticulum (ER)–derived structures, each of which has specific functions. The ER body found in Arabidopsis thaliana is a spindle-shaped structure that specifically accumulates high levels of PYK10/BGLU23, a β-glucosidase that bears an ER-retention signal. The molecular mechanisms underlying the formation of the ER body remain obscure. We isolated an ER body–deficient mutant in Arabidopsis seedlings that we termed nai2. The NAI2 gene (At3g15950) encodes a member of a unique protein family that is only found in the Brassicaceae. NAI2 localizes to the ER body, and a reduction in NAI2 gene expression elongates ER bodies and reduces their numbers. NAI2 deficiency does not affect PYK10 mRNA levels but reduces the level of PYK10 protein, which becomes uniformly diffused throughout the ER. NAI1, a transcription factor responsible for ER body formation, regulates NAI2 gene expression. These observations indicate that NAI2 is a key factor that enables ER body formation and the accumulation of PYK10 in ER bodies of Arabidopsis. Interestingly, ER body–like structures are also restricted to the Brassicales, including the Brassicaceae. NAI2 homologs may have evolved specifically in Brassicales for the purpose of producing ER body–like structures.